Common variable immunodeficiency (CVID) presenting with malabsorption due to giardiasis - Kevser ONBAŞI,; Fulya GÜNŞAR,; Aytül Z. SİN,; Ömür ARDENİZ,; Ali KOKULUDAĞ,; Filiz SEBİK, (Turkish Journal of Gastroenterology, 2019)
-